Gastric Tuft Cells Express DCLK1, and Increase in Hyperplasia - Saqui-Salces, Milena (2011)
Epithelial tuft cells are named for their characteristic microtubule bundle located at the cell apex where it is exposed to the luminal environment. As such, tuft cells are found in multiple organs, including the gastrointestinal (GI) tract where the apical “tuft” is hypothesized to detect and transmit environmental signals. Thus, the goal of our study was to characterize gastric tuft cells during GI tract development, then subsequently in the normal and metaplastic adult stomach. GI tracts from mouse embryos, newborn and post-natal mice were analyzed. Tuft cells were identified by immunohistochemistry using acetylated-α-tubulin (acTub) antibody to detect the microtubule bundle. Additional tuft cell markers, e.g., doublecortin-like kinase 1 (DCLK1), were used to co-localize with acTub. Tuft cells were quantified in human gastric tissue arrays and in mouse stomachs with or without inflammation. In the developing intestine, tuft cells in both the crypts and villi expressed all markers by E18.5. In the stomach, acTub co-localized with DCLK1 and other established tuft cell markers by E18.5 in the antrum but not until postnatal day 7 in the corpus, with the highest density of tuft cells clustered at the forestomach ridge. Tuft cell numbers increased in hyperplastic human and mouse stomachs. In the adult GI tract, the tuft cell marker acTub co-expressed with DCKL1 and chemosensory markers, e.g., TRPM5. In summary, tuft cells appear in the gastric antrum and intestine at E18.5, but their maximal numbers in the corpus are not achieved until after weaning. Tuft cell numbers increase with inflammation, hyperplasia and metaplasia.